El poblamiento romano en el área de Yecla (Murcia) - Ruiz Molina, Liborio (Antigüedad y Cristianismo, 1998)
A study of the Roman sttlement in Yecla (as in every other site) should be done with relation to al1 the settlements in the Roman period. History of the investigation. Phisical characteristics of the area. The Roman settlement is described according to the following scheme: indigenous antecedents; the centres of population from the first to the fifth century; Roman roads. Modifications of the settlement during the sixth and seventh centuries.